ANALYSIS OF FACTORS AFFECTING MANAGERIAL PERFORMANCE SKPD IN NORTH SUMATERA PROVINCIAL GOVERNMENT WITH INTERNAL CONTROL AS MODERATING VARIABLES - Indra Gunawan, suhaimi (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to examine some factors which influenced Managerial Performance in SKPD (Regional Work Unit) in the North Sumatera Provincial Administration with Internal Control as moderating variable. Primary data were gathered by using questionnaires. The research used qualitative causal associative method. The population was 755 managers in the Secretariat of SKPD consisted of echelon IV, echelon III, and echelon II, and 261 of them from 39 SKPDs were used as the samples, taken by using Slovin formula. The data were analyzed by using multiple linear regression analysis and residual test. The result of the research showed that, simultaneously, the variables of Participation in Budgeting, Budget Target Clarity, Decentralization Structure, Quality of Human Resources, and Performance-Based Budget Application had significant influence on SKPD Managerial Performance, while the variable of Decentralization Structure did not have any influence on SKPD Managerial Performance. The result of residual test showed that Internal Control could not moderate the correlation of Participation in Budgeting, Budget Target Clarity, Decentralization Structure, Quality of Human Resources, and Performance-Based Budget Application with SKPD Managerial Performance in the North Sumatera Provincial Administration.